DEVELOPMENT OF EDUCATIONAL LEXICAL COMPETENCIES OF FUTURE TEACHERS (Conferencea, 2024)
This article talks about the lexical competencies and communication feautures of future pedagogues. Methods which helps to enrich the imagination of students.